A Semi-autoethnographical Account of the Order of Malta’s Annual Pilgrimage to Lourdes - Munro, Dane (The international journal of religious tourism and pilgrimage, 2022)
Lourdes, in the French Pyrenees, has been a pilgrimage site since 1858. At present, about six million Roman Catholic pilgrims and others visit Lourdes every year. During the annual weeklong pilgrimage of the Order of St John, an average of about 7,500 participants from 45 countries, including 380 doctors, nurses and pharmacists, 250 priests and other volunteers, are nursing and caring for 1,500 malades (the sick and suffering). This semi-autoethnographical account is based on many years of visitation as a member of the Order of St John and describes the various changes of a political and societal nature, while the core values of healing and the emphasis on reverence have remained unchanged.